2011
DOI: 10.1111/j.1600-0404.2011.01563.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cardiovascular disease risk factors in restless legs syndrome

Abstract: Our findings argue against the presence of an altered lipid metabolism as a risk factor for the development of cerebrovascular disease in patients with RLS, even if they do support the idea that cerebrovascular disease might be frequent in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Obstructive sleep apnea is one such condition, which is potentially relevant here for several reasons. It has been shown that in the case of hypercholesterolemia, the apparent association with RLS is fully explained by comorbid sleep apnea (Cosentino et al, 2012). Furthermore, because leg actigraphy cannot distinguish between idiopathic PLMs and periodic leg movements accompanying respiratory events, it is possible that some of the PLMs detected in our study were movements co-occurring with sleep apnea that were incorrectly classified because of the lack of polysomnographic monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea is one such condition, which is potentially relevant here for several reasons. It has been shown that in the case of hypercholesterolemia, the apparent association with RLS is fully explained by comorbid sleep apnea (Cosentino et al, 2012). Furthermore, because leg actigraphy cannot distinguish between idiopathic PLMs and periodic leg movements accompanying respiratory events, it is possible that some of the PLMs detected in our study were movements co-occurring with sleep apnea that were incorrectly classified because of the lack of polysomnographic monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 20 studies, 15 suggested an increased risk of hypertension, CVD, CAD, cerebrovascular disease, or heart disease in patients with RLS/PLMS [2, 10, 14, 16, 40, 61, 71, 78, 84, 87, 97, 121, 132, 136, 137]. Five cross-sectional epidemiologic studies reported no associated or a reduced risk of hypertension and CVD compared to patients without RLS [30, 55, 101, 141, 142]. As with the prospective and observational studies, the differences in the outcomes from the cross-sectional epidemiologic studies may be attributed to differences in sample populations, diagnostic criteria for RLS, and the consideration of disease duration and severity.…”
Section: The Evidence For An Association Between Rls/plms and Hypertementioning
confidence: 99%
“…Many studies have shown that RLS is associated with an increased risk for cardiovascular and/or cerebrovascular disease [11][12][13] though there have been contradictory results [26,27]. Some potential mechanisms such as physiological, cardiac, cerebral, and inflammatory were suggested as causing increased risks for vascular disease in RLS [28][29][30].…”
Section: Discussionmentioning
confidence: 96%
“…The IRLSS is the Bgold standardt o clinically evaluate RLS symptom severity and its impact on activities of daily life. The total score from the 10 items is used to indicate Bmild^(1-10), Bmoderate^ (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), Bsevere^ (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and Bvery severe^(31-40) RLS symptoms [24].…”
Section: International Rls Rating Scale (Irlss)mentioning
confidence: 99%